IBC battery silver paste and IBC battery
By adding organic adhesives of polymer and rosin to the silver paste of IBC batteries, the problem of silver paste being interrupted and fall off during high pressure and rapid printing in the prior art is solved, and a higher bonding effect is achieved. Battery efficiency.
Patent Information
- Application Number
- CN202310922497.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing IBC battery silver paste is prone to breaking and falling off during high pressure and rapid printing, which affects the efficiency and yield of the battery.
An IBC battery silver paste including organic additives, silver powder, glass powder and organic binder is used, wherein the organic binder comprises a polymer and a rosin. This silver paste is quickly cooled after printing into a negative electrode fine grid, improving the bonding effect and making the negative electrode fine grid surface smoother, reducing the risk of shedding.
It effectively solves the problem of IBC battery silver paste being interrupted and fall off during high pressure and rapid printing, and improves the efficiency and yield of the battery.
Smart Images

Figure CN119400478A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of crystalline silicon solar cell manufacturing, and in particular to an IBC cell silver paste and an IBC cell. Background Art
[0002] The interdigitated back contact (IBC) battery is a new type of battery in which the contact electrodes of the P / N junction, substrate and emitter region are made in an interdigitated shape on the back of the battery. Its core technology is to prepare high-quality p-region and n-region arranged in an interdigitated shape on the back of the battery, and then print aluminum paste connected to the p-region to form the positive electrode grid line, and print silver paste connected to the n-region to form the negative electrode grid line.
[0003] At present, the order of printing the grid lines of IBC batteries is: printing the main grid - drying - printing silver paste in the n-region to form a silver fine grid - drying - printing the aluminum fine grid in the p+ region; in the process of printing the aluminum fine grid after the silver fine grid is printed and dried, the silver fine grid is very likely to break or fall off during the high pressure and fast printing process, which seriously affects the efficiency and yield of the battery. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an IBC battery silver paste and an IBC battery, so as to solve the problem that the negative electrode silver fine grid formed by the existing IBC battery silver paste is prone to grid breakage and falling off during high pressure and rapid printing, thereby affecting the efficiency and yield of the battery.
[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:
[0006] The present invention provides an IBC battery silver paste, wherein the components constituting the silver paste include organic additives, silver powder, glass powder and an organic binder, and the organic binder includes a high molecular polymer and rosin.
[0007] Furthermore, in the IBC battery silver paste, the mass percentage of the organic additive is 0.6-1.2%; the mass percentage of the silver powder is 78-82%; the mass percentage of the glass powder is 1.5-2.2%; and the mass percentage of the organic binder is 13.6-19.4%.
[0008] Furthermore, in the IBC battery silver paste, the mass percentage of the high molecular polymer in the organic binder is 8-10%, and the mass percentage of the rosin is 1-3%.
[0009] Furthermore, in the IBC battery silver paste, the high molecular polymer includes at least one of polyethylene and polyvinyl chloride.
[0010] Furthermore, in the IBC battery silver paste, the organic additive includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate.
[0011] Furthermore, in the IBC battery silver paste, the silver powder includes 88-95% by mass of micron-spherical silver powder and 5-12% by mass of nano-spherical silver powder.
[0012] Furthermore, in the IBC battery silver paste, the organic binder also includes an organic solvent;
[0013] The mass fraction of the organic solvent in the organic binder is 87-91%.
[0014] Furthermore, in the IBC battery silver paste, the organic solvent is at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.
[0015] Furthermore, in the IBC battery silver paste, the glass powder is obtained by sintering and crushing 20-22% Bi2O3, 6-10% Al2O3, 8-12% SiO2, 5-25% ZnO, 15-20% Sb2O5, 5-10% TiO, 3-8% B2O3, 3-10% MgO, and 15-20% TeO3 in mass percentage.
[0016] The present invention also proposes an IBC battery, wherein a plurality of negative electrode fine grids are attached to the back of the IBC battery, and the negative electrode fine wires are prepared from the above-mentioned silver paste.
[0017] Compared with the prior art, the embodiments of the present invention have the following advantages:
[0018] In the embodiment of the present invention, the silver paste for IBC battery provided comprises organic additives, silver powder, glass powder and organic binder, wherein the organic binder comprises high molecular polymer and rosin. By adding rosin to the silver paste, not only can the negative electrode fine grid be quickly cooled after printing, thereby improving the bonding effect, but also the surface of the formed negative electrode fine grid can be made smoother and not easy to fall off due to transportation, friction, etc., thus solving the problem that the existing silver paste is prone to breaking and falling off during high pressure and fast printing after forming the negative electrode fine grid of the IBC battery, thus affecting the efficiency and yield of the battery.
[0019] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a flow chart of the method for preparing IBC battery silver paste provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0022] An embodiment of the present invention provides an IBC battery silver paste, wherein the components constituting the silver paste include organic additives, silver powder, glass powder and an organic binder, wherein the organic binder includes a high molecular polymer and rosin.
[0023] The IBC battery silver paste provided in the embodiment of the present invention is used to form the negative electrode grid lines of the IBC battery, specifically to form the negative electrode fine grid lines of the IBC battery.
[0024] Among them, silver powder is the main component, and the silver paste has good thermal conductivity, electrical conductivity and burn-through performance. When the silver paste is printed on the anti-reflection film layer on the back of the silicon wafer, the silicon nitride film and the silicon oxide film in the passivation layer can be burned through in sequence, and then contact the n+ doped area to form a negative gate line, so there is no need to laser open the n+ doped area, avoiding the damage of the passivation layer of the n+ doped area caused by laser grooving;
[0025] Among them, glass powder is an inorganic adhesive, which will melt into liquid under high temperature conditions and condense when cooled to play a bonding role; organic additives can reduce the overall viscosity of silver paste; the high molecular polymer in the organic binder can ensure the overall bonding effect, and the rosin therein can not only accelerate the cooling rate of the silver paste after printing into the negative electrode fine grid, improve the bonding effect, but also make the surface of the formed negative electrode fine grid smoother and not easy to fall off due to transportation, friction, etc., thus solving the problem that the existing silver paste is prone to breakage and falling off during high pressure and rapid printing after forming the negative electrode fine grid of the IBC battery, affecting the efficiency and yield of the battery.
[0026] Optionally, in one embodiment, in the above silver paste, the mass percentage of organic additives is 0.6-1.2%; the mass percentage of silver powder is 78-82%; the mass percentage of glass powder is 1.5-2.2%; and the mass percentage of organic binder is 13.6-19.4%.
[0027] For example, in the silver paste, the mass fractions of the organic additive, silver powder, glass powder and organic binder are 0.6%, 80%, 1.8% and 17.6% respectively.
[0028] For example, in the silver paste, the mass fractions of the organic additive, silver powder, glass powder and organic binder are 1.2%, 78%, 2.2% and 18.6% respectively.
[0029] For example, in the silver paste, the mass fractions of the organic additive, silver powder, glass powder and organic binder are 0.9%, 82%, 1.5% and 15.6% respectively.
[0030] For example, in the silver paste, the mass fractions of the organic additive, silver powder, glass powder and organic binder are 1.2%, 82%, 2.2% and 14.6% respectively.
[0031] For example, in the silver paste, the mass fractions of the organic additive, silver powder, glass powder and organic binder are 0.6%, 78%, 1.5% and 19.5% respectively.
[0032] Optionally, in one embodiment, the mass percentage of the high molecular weight polymer in the organic binder is 8-10%, and the mass percentage of the rosin is 1-3%.
[0033] The above-mentioned high molecular polymer includes at least one of polyethylene and polyvinyl chloride, and may also include ethyl cellulose N50 and the like.
[0034] Optionally, in one embodiment, the silver powder includes 88-95% by mass of micron-sized spherical silver powder and 5-12% by mass of nano-sized spherical silver powder. Since there are gaps between the micron-sized silver powder and the silver powder, the nano-sized spherical silver powder can just fill and penetrate into the gaps between the micron-sized silver powder and the silver powder.
[0035] Optionally, in one embodiment, the organic additive includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, lauryl alcohol phosphate, and BYK110.
[0036] In the IBC battery silver paste provided in the embodiment of the present invention, the above-mentioned organic binder also includes an organic solvent; wherein the high molecular polymer and rosin are dissolved in the organic solvent, so that the organic solvent can be used as an organic binder, that is, the paste plays a role of bonding powder after drying.
[0037] Optionally, in one embodiment, the mass fraction of the organic solvent in the organic binder is 87-91%.
[0038] The organic solvents are at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.
[0039] Optionally, in one embodiment, the glass powder is obtained by sintering and crushing 20 to 22 parts of Bi2O3, 6 to 10 parts of Al2O3, 8 to 12 parts of SiO2, 5 to 29 parts of ZnO, 15 to 20 parts of Sb2O5, 5 to 10 parts of TiO, 3 to 8 parts of B2O3, 3 to 10 parts of MgO, and 15 to 20 parts of TeO3, by mass, and the D50 of the glass powder is 1.5 to 1.8 μm. If D50 is less than 1.5 μm, the glass activity is too high, and if D50 is greater than 1.8 μm, the glass activity is too low.
[0040] Among them, Bi2O3 is the main network structure, ZnO can break the network structure and promote glass crystallization, Al2O3 can adjust the glass stability and increase the viscosity; SiO2 is used as a glass network former to promote glass stability and increase the glass melting point; Sb2O5 is used to clarify and uniform the glass liquid; TiO2 is used for local crystallization, B2O3 is a network body, MgO is used to lower the melting point, and TeO3 lowers the glass formation temperature.
[0041] The present invention also provides a method for preparing an IBC battery silver paste, wherein: Figure 1 As shown, it includes steps 101 to 102:
[0042] Step 101, mixing silver powder, organic binder and glass powder to obtain a mixture; wherein the organic binder includes a high molecular polymer and rosin;
[0043] Step 102: Grind the mixture, add an organic additive, and obtain IBC battery silver paste.
[0044] In the above step 101, 78-82% of silver powder, 14.6-19.5% of organic binder, and 1.5-2.2% of glass powder accounting for the total mass of the raw materials are weighed and mixed, and dispersed by a disperser to obtain the above mixture.
[0045] Optionally, in one embodiment, the silver powder includes 88-95% by mass of micron spherical silver powder and 5-12% by mass of nano spherical silver powder; in the above step 101, the organic binder and the nano spherical silver powder are first mixed and fractionated using a disperser, and then the micron spherical silver powder and glass powder are added, dispersed again using a disperser, and then ground to obtain the above mixture.
[0046] In the above step 102, the above mixture is ground and then an organic additive accounting for 0.6-1.2% of the total mass of the raw materials is added, and after high-speed dispersion, a silver paste for forming fine grid lines of the negative electrode of an IBC battery is obtained.
[0047] In the embodiment of the present invention, by adding rosin to the silver paste, not only can the negative electrode fine grid be quickly cooled after printing to improve the bonding effect, but the surface of the formed negative electrode fine grid can also be made smoother and not easily fall off due to transportation, friction, etc., thereby solving the problem that the existing silver paste is prone to breakage and falling off during high pressure and rapid printing after forming the negative electrode fine grid of the IBC battery, thereby affecting the efficiency and yield of the battery.
[0048] Optionally, in the preparation method provided in the embodiment of the present invention, the mass percentage of the high molecular weight polymer in the organic adhesive is 8-10%, and the mass percentage of the rosin is 1-3%.
[0049] Optionally, in the preparation method provided in an embodiment of the present invention, the high molecular polymer includes at least one of polyethylene and polyvinyl chloride.
[0050] Optionally, in the preparation method provided in an embodiment of the present invention, the organic additive includes two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate.
[0051] Optionally, in the preparation method provided in the embodiment of the present invention, the silver powder includes 88-95% by mass of micron spherical silver powder and 5-12% by mass of nano spherical silver powder.
[0052] Optionally, in the preparation method provided in the embodiment of the present invention, the organic binder further includes an organic solvent;
[0053] The mass fraction of the organic solvent in the organic binder is 87-91%.
[0054] Optionally, in the preparation method provided in an embodiment of the present invention, the organic solvent is at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.
[0055] Optionally, in the preparation method provided in an embodiment of the present invention, the glass powder is obtained by sintering and crushing 20-22% Bi2O3, 6-10% Al2O3, 8-12% SiO2, 5-25% ZnO, 15-20% Sb2O5, 5-10% TiO, 3-8% B2O3, 3-10% MgO, and 15-20% TeO3 in mass percentage.
[0056] The present invention also proposes an IBC battery, wherein a plurality of negative electrode fine grids are attached to the back of the IBC battery, and the negative electrode fine wires are prepared from the above-mentioned silver paste.
[0057] The present invention is described in detail below by way of examples.
[0058] Example 1
[0059] (1) Providing silver paste a1: In parts by mass, the IBC battery silver paste a1 is composed of 0.6 parts of organic additives, 80 parts of silver powder, 2 parts of glass powder and 17.6 parts of organic binder;
[0060] Among them, the above-mentioned organic additives are silane coupling agent and lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 9s and a mass fraction of 90% and nano-grade spherical silver powder with a purity of 3 9s and a mass fraction of 10%; the organic binder includes ethyl cellulose-N50 with a mass fraction of 9%, ethyl cellulose-N50 with a mass fraction of 1% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, diethyl phthalate, pine alcohol, butyl carbitol acetate and tributyl citrate; the glass powder is obtained by sintering and crushing 20% Bi2O3, 8% Al2O3, 10% SiO2, 6% ZnO, 18% Sb2O5, 8% TiO, 7% B2O3, 8% MgO, and 15% TeO3 by mass percentage, and the D50 of the glass powder is 1.5-1.8μm.
[0061] (2) The silver paste a1 is printed on the n-type doped region of an IBC silicon wafer with a size of 182 mm × 182 mm through a 480 mesh screen to form a negative electrode fine grid, and then sintered in a sintering furnace with a peak sintering temperature of 778° C. to obtain an IBC battery.
[0062] After sintering, the photoelectric conversion efficiency was tested to be 25.145%, and the gate breaking rate was 0.08%.
[0063] Example 2
[0064] (1) Providing silver paste a2: In parts by mass, the IBC battery silver paste a2 is composed of 1.2 parts of organic additives, 78 parts of silver powder, 2.2 parts of glass powder and 18.6 parts of organic binder;
[0065] Among them, the above-mentioned organic additives are silane coupling agent and lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 9s and a mass fraction of 88% and nano-grade spherical silver powder with a purity of 3 9s and a mass fraction of 12%; the organic binder includes ethyl cellulose-N50 with a mass fraction of 8%, ethyl cellulose-N50 with a mass fraction of 1% and an organic solvent with a mass fraction of 91%, and the organic solvent is composed of benzyl alcohol, diethyl phthalate, pine alcohol, butyl carbitol acetate and tributyl citrate; the glass powder is obtained by sintering and crushing 20% Bi2O3, 8% Al2O3, 10% SiO2, 6% ZnO, 18% Sb2O5, 8% TiO, 7% B2O3, 8% MgO, and 15% TeO3 by mass percentage, and the D50 of the glass powder is 1.5-1.8μm.
[0066] (2) The silver paste a2 is printed on the n-type doped region of an IBC silicon wafer with a size of 182 mm × 182 mm through a 480 mesh screen to form a negative electrode fine grid, and then sintered in a sintering furnace with a peak sintering temperature of 778° C. to obtain an IBC battery.
[0067] After sintering, the photoelectric conversion efficiency was tested to be 25.212% and the gate breaking rate was 0.07%.
[0068] Example 3
[0069] (1) Providing silver paste a3: In parts by mass, the IBC battery silver paste a3 is composed of 0.9 parts of organic additives, 82 parts of silver powder, 1.5 parts of glass powder and 15.6 parts of organic binder;
[0070] Among them, the above-mentioned organic additives are silane coupling agent and lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 9s and a mass fraction of 95% and nano-grade spherical silver powder with a purity of 3 9s and a mass fraction of 5%; the organic binder includes ethyl cellulose-N50 with a mass fraction of 10%, ethyl cellulose-N50 with a mass fraction of 3% and an organic solvent with a mass fraction of 87%, and the organic solvent is composed of benzyl alcohol, diethyl phthalate, pine alcohol, butyl carbitol acetate and tributyl citrate; the glass powder is obtained by sintering and crushing 20% Bi2O3, 8% Al2O3, 10% SiO2, 6% ZnO, 18% Sb2O5, 8% TiO, 7% B2O3, 8% MgO, and 15% TeO3 by mass percentage, and the D50 of the glass powder is 1.5-1.8μm.
[0071] (2) The silver paste a3 is printed on the n-type doped region of an IBC silicon wafer with a size of 182 mm × 182 mm through a 480 mesh screen to form a negative electrode fine grid, and then sintered in a sintering furnace with a peak sintering temperature of 778° C. to obtain an IBC battery.
[0072] After sintering, the photoelectric conversion efficiency was tested to be 25.135%, and the gate breaking rate was 0.065%.
[0073] Example 4
[0074] (1) Providing silver paste a4: In parts by mass, the IBC battery silver paste a4 is composed of 1.2 parts of organic additives, 82 parts of silver powder, 2.2 parts of glass powder and 14.6 parts of organic binder;
[0075] Among them, the above-mentioned organic additives are silane coupling agent and lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 9s and a mass fraction of 90% and nano-grade spherical silver powder with a purity of 3 9s and a mass fraction of 10%; the organic binder includes ethyl cellulose-N50 with a mass fraction of 9%, ethyl cellulose-N50 with a mass fraction of 1% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, diethyl phthalate, pine alcohol, butyl carbitol acetate and tributyl citrate; the glass powder is obtained by sintering and crushing 20% Bi2O3, 8% Al2O3, 10% SiO2, 6% ZnO, 18% Sb2O5, 8% TiO, 7% B2O3, 8% MgO, and 15% TeO3 by mass percentage, and the D50 of the glass powder is 1.5-1.8μm.
[0076] (2) The silver paste a4 is printed on the n-type doped region of an IBC silicon wafer with a size of 182 mm × 182 mm through a 480 mesh screen to form a negative electrode fine grid, and then put into a sintering furnace for sintering at a peak temperature of 778° C. to obtain an IBC battery.
[0077] After sintering, the photoelectric conversion efficiency was tested to be 25.145%, and the gate breaking rate was 0.062%.
[0078] Example 5
[0079] (1) Providing silver paste a5: In parts by mass, the IBC battery silver paste a5 is composed of 0.6 parts of organic additives, 78 parts of silver powder, 1.5 parts of glass powder and 19.5 parts of organic binder;
[0080] Among them, the above-mentioned organic additives are silane coupling agent and lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 9s and a mass fraction of 90% and nano-grade spherical silver powder with a purity of 3 9s and a mass fraction of 10%; the organic binder includes ethyl cellulose-N50 with a mass fraction of 9%, ethyl cellulose-N50 with a mass fraction of 1% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, diethyl phthalate, pine alcohol, butyl carbitol acetate and tributyl citrate; the glass powder is obtained by sintering and crushing 20% Bi2O3, 8% Al2O3, 10% SiO2, 6% ZnO, 18% Sb2O5, 8% TiO, 7% B2O3, 8% MgO, and 15% TeO3 by mass percentage, and the D50 of the glass powder is 1.5-1.8μm.
[0081] (2) The silver paste a5 is printed on the n-type doped region of an IBC silicon wafer with a size of 182 mm × 182 mm through a 480 mesh screen to form a negative electrode fine grid, and then sintered in a sintering furnace with a peak sintering temperature of 778° C. to obtain an IBC battery.
[0082] After sintering, the photoelectric conversion efficiency was tested to be 25.214% and the gate breaking rate was 0.06%.
[0083] Comparative Example 1
[0084] (1) Providing silver paste b1: In parts by mass, the IBC battery silver paste b1 is composed of 0.6 parts of organic additives, 80 parts of silver powder, 2 parts of glass powder and 17.6 parts of organic binder;
[0085] Among them, the above-mentioned organic additives are silane coupling agent and lauryl alcohol phosphate; the silver powder includes micron-grade spherical silver powder with a purity of 3 9s and a mass fraction of 90% and nano-grade spherical silver powder with a purity of 3 9s and a mass fraction of 10%; the organic binder includes ethyl cellulose-N50 with a mass fraction of 10% and an organic solvent with a mass fraction of 90%, and the organic solvent is composed of benzyl alcohol, diethyl phthalate, pinene alcohol, butyl carbitol acetate and tributyl citrate; the glass powder is obtained by sintering and crushing 20% Bi2O3, 8% Al2O3, 10% SiO2, 6% ZnO, 18% Sb2O5, 8% TiO, 7% B2O3, 8% MgO, and 15% TeO3 by mass percentage, and the D50 of the glass powder is 1.5-1.8μm.
[0086] (2) The boron-aluminum paste is printed on the n-type doped region of an IBC silicon wafer with a size of 182 mm × 182 mm through a 480-mesh screen to form a negative electrode fine grid, and then sintered in a sintering furnace with a peak sintering temperature of 778° C. to obtain an IBC battery.
[0087] After sintering, the photoelectric conversion efficiency was tested to be 25.07% and the gate breaking rate was 0.12%.
[0088] By comparing Examples 1 to 5 with Comparative Example 1, it can be seen that the efficiency of the negative electrode fine grid formed by printing the silver paste doped with rosin is the same as that of the IBC battery silver paste without adding rosin, the broken grid ratio is reduced by 0.5%, and there is no shedding phenomenon.
[0089] In summary, in this embodiment, by adding rosin to the silver paste, not only can the negative electrode fine grid be quickly cooled after printing to improve the bonding effect, but the surface of the formed negative electrode fine grid can also be made smoother and not easily fall off due to transportation, friction, etc., thereby solving the problem that the existing silver paste is prone to breakage and falling off during high pressure and rapid printing after forming the negative electrode fine grid of the IBC battery, thereby affecting the efficiency and yield of the battery.
[0090] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0091] The above is a detailed introduction to an IBC battery silver paste and an IBC battery provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for general technicians in this field, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. An IBC battery silver paste, characterized in that: The components constituting the silver paste include organic additives, silver powder, glass powder and organic adhesive, and the organic adhesive includes high molecular polymer and rosin.
2. The IBC battery silver paste according to claim 1, characterized in that: The mass percentage of the organic additive is 0.6-1.2%; the mass percentage of the silver powder is 78-82%; the mass percentage of the glass powder is 1.5-2.2%; and the mass percentage of the organic binder is 14.6-19.5%.
3. The IBC battery silver paste according to claim 1, characterized in that: The mass percentage of the high molecular polymer in the organic adhesive is 8-10%, and the mass percentage of the rosin is 1-3%.
4. The IBC battery silver paste according to claim 1, characterized in that: The high molecular polymer includes at least one of polyethylene and polyvinyl chloride.
5. The IBC battery silver paste according to claim 1, characterized in that: The organic additives include two or more of fatty alcohol ether phosphate, aluminate coupling agent, silane coupling agent, zirconium aluminate coupling agent, lauryl phosphate, silicone oil, dibasic acid ester, and lauryl alcohol phosphate.
6. The IBC battery silver paste according to claim 1, characterized in that: The silver powder comprises 88-95% by mass of micron-spherical silver powder and 5-12% by mass of nano-spherical silver powder.
7. The IBC battery silver paste according to claim 1, characterized in that: The organic binder also includes an organic solvent; The mass fraction of the organic solvent in the organic binder is 87-91%.
8. The IBC battery silver paste according to claim 7, characterized in that: The organic solvent is at least five of benzyl alcohol, diethyl phthalate, terpineol, butyl carbitol, butyl carbitol acetate, tributyl citrate, Span 85 and alcohol ester twelve.
9. The IBC battery silver paste according to claim 1, characterized in that: The glass powder is obtained by sintering and crushing 20-22% Bi2O3, 6-10% Al2O3, 8-12% SiO2, 5-25% ZnO, 15-20% Sb2O5, 5-10% TiO, 3-8% B2O3, 3-10% MgO and 15-20% TeO3 in mass percentage.
10. An IBC battery, characterized in that: A plurality of negative electrode fine grids are attached to the back of the IBC battery, and the negative electrode fine wires are prepared from the silver paste described in any one of claims 1 to 9.
Citation Information
Patent Citations
Solar cell sizing agent applied to fine line printing and preparation method thereof
CN109378109A
N-type TOPCon battery back polishing silver paste and preparation method and application thereof
CN114373568A
IBC battery aluminum paste, IBC battery and preparation method of IBC battery
CN116344096A